2017
DOI: 10.3389/fped.2017.00084
|View full text |Cite
|
Sign up to set email alerts
|

Review: Quality of Life in Children with Non-cystic Fibrosis Bronchiectasis

Abstract: Non-cystic fibrosis bronchiectasis (NCFB) has gained renewed interest, due to its increasing health-care burden. Annual mortality statistics in England and Wales showed that under 1,000 people die from bronchiectasis each year, and this number is increasing by 3% yearly. Unfortunately, there is a severe lack of well-powered, randomized controlled trials to guide clinicians how to manage NCFB effectively. Quality-of-life (QOL) measures in NCFB are an important aspect of clinical care that has not been studied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…The exacerbations in PCD, defined as an acute increase in respiratory symptoms [14], are predictors of severity of disease and poor quality of life [10] and negatively impact on lung function, as bacterial infections are associated with morbidity and mortality in these patients [13]. It was reported that about 25% of children with PCD fail to recover to baseline lung function within 3 months following a pulmonary exacerbation treated with intravenous antibiotics and may never regain pre-exacerbation spirometry [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exacerbations in PCD, defined as an acute increase in respiratory symptoms [14], are predictors of severity of disease and poor quality of life [10] and negatively impact on lung function, as bacterial infections are associated with morbidity and mortality in these patients [13]. It was reported that about 25% of children with PCD fail to recover to baseline lung function within 3 months following a pulmonary exacerbation treated with intravenous antibiotics and may never regain pre-exacerbation spirometry [15].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory infections are major determinants of morbidity and mortality in patients with PCD, as they are correlated to a poor quality of life [10] and to functional decline [11]. Haemophilus influentiae and Streptococcus pneumoniae appear to be the most common pathogens isolated from patients with PCD during early childhood [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…CC‐QoL questionnaire for older children able to self‐report . Relationship between QoL measures and other bronchiectasis markers of severity…”
Section: Monitoringmentioning
confidence: 99%
“…Given the difficulties of direct reporting for children of preschool age, parent‐proxy reporting is often the practice of choice. Parent‐proxy cough‐specific QoL (PC‐QoL) is the commonly used tool in paediatric studies . For older children (>7 years), a child self‐reporting instrument, chronic cough‐specific QoL (CC‐QoL) questionnaire is a more reliable and sensitive HR‐QoL from the child's perspective …”
Section: Monitoringmentioning
confidence: 99%
“…NCBE are associated with comorbidities such as anxiety, depression, and fatigue [25]. Reduced quality of life due to respiratory symptoms and decreasing ability to participate in activities of daily living have been reported in NCBE [13,25,29].…”
Section: Introductionmentioning
confidence: 99%